Determining the real site of peroneal nerve injury with knee dislocation: Earlierier is easier. Issue 10 (October 2021) - Hughes, Benedict A.; Stallard, Joseph; Chakrabarty, Aruna; Anand, Sanjeev; Bourke, Grainne
Abstract: Common peroneal nerve (CPN) injury is a recognised complication of traumatic knee dislocation with a direct association between the degree of ligamentous injury and the degree of CPN injury. It is essential explore and repair these injuries in good time to reduce morbidity. Often exploration only involves the portion of this nerve associated with the joint as it courses around the fibular head. However, a recent case highlighted the importance of proximal exploration to its branching point from the sciatic nerve, a known point of fragility, even if other defects have been identified.